Kombinasi Metode SWARA dan SMART Dalam Sistem Pendukung Keputusan Pemilihan Guru Berprestasi - Heri Bambang Santoso; I Wayan Sriyasa; Puspa Citra (PT. Tech Cart Press, 2024)
The selection of outstanding teachers is an important process in the education system to recognize and reward the dedication and outstanding contributions of educators. Problems in the selection of outstanding teachers include unclear selection criteria, subjectivity in assessment, limited resources, and fairness and transparency in the selection process. One of the main problems is the inconsistent or inadequate definition of criteria, which can result in unclarity in determining who is worthy of being an outstanding teacher. This study aims to select outstanding teachers by applying a combination of SWARA and SMART methods in the assessment process of outstanding teachers, so that the tone of application of this method can help the school in determining outstanding teachers. The ranking results show that rank 1 was obtained on behalf of Teacher HS with a value of 0.77105, rank 2 was obtained on behalf of Teacher IA with a value of 0.76975, and rank 3 was obtained on behalf of Teacher HSR with a value of 0.73025.